Geomathematical evaluation of the banded iron formations of the Bonito Mine (Northeastern Brazil): Several approaches through multivariate analysis, geostatistical assessment and 3-D geological modeling - Fonteles, Helano Regis da Nóbrega (2019)
This research was focused on the Banded Iron Formations (BIF) of the Bonito Mine. The database is stemmed from an exhaustive drilling program at the mining site. Therefore, hundreds of iron ore samples were assayed for Fe2O3, SiO2, Al2O3, P and Mn grades, and qualitative geotechnical data such as weathering grades, physical ore type, voids, and coring depth levels were collected from drilling core samples. The Seridó Group (634 ± 10 Ma) was divided from base to top: (a) Serra do Quintos Formation (NPsq), composed of ferruginous quartzites, hematite and/or magnetite itabirites, garnet-tremolite schist, muscovite-quartzite, gneiss, actinolite-schist with magnetite and, in some places, metaultramafics, metamafics and leucogneiss; (b) Jucurutu Formation (NPj), composed mainly by paragneisses, with intercalations of a basal conglomerate, marbles, calc-silicate rocks, mica-schist, quartzite, iron formations, metavolcanics and metacherts; (c) Equador Formation, predominantly composed of muscovite-quartzite with arkosic facies containing interbedded polimitic metaconglomerates, and (d) the Seridó Formation, which is formed of feldspathic mica schists or aluminous medium to high grade metamorphic facies on the most part of the unit. Locally, marbles, calc-silicate rocks, quartzite, and metavolcanics are interbedded in the main lithotype. A previous petrographic study has shown that there are four BIF types: amphibolitic itabirites, martitic itabirites, hematitic itabirites, and magnetitic itabirites. In order to enhance this study, a multivariate model using geochemical and geotechnical data under a systemic approach was employed. This approach was conceived to account for the whole available information, both quantitative and qualitative, through the Correspondence Analysis and Cluster Analysis grounded appropriate methodology. Another goal of this study was the classification scheme of BIFs based on major oxides grades (wt.%) and REE data ratio used for the construction of bivariate and ternary diagrams regarding the tectonic environments of the BIF deposits. The major goal of the analysis was the identification of the tectonic setting of some well-representative BIF deposits and search for a geological correlation based on metallogenic origin. A study aiming to the delineation of the mineralized thickness was performed using geostatistical estimation (simples and ordinary kriging) and simulation (Gaussian, direct sequential and simulated annealing) methods to map this geological attribute. We have demonstrated that the banded iron formations thicker areas may correspond to the antiform fold as the dominant tectonic feature at the mining site. Geological modeling was executed to compose the lithological package encompassed by the Bonito Mine study area. The relevant information obtained from the rounds of geomodeling is comprised of interbedded magmatic rocks (basic and acid intrusive and volcanic rocks) and the less voluminous rocks such as phyllite, ferruginous quartzite, and mylonite. The geologic solids were generated by voxels modeling through the lithoblending algorithm. The same methodology was applied to the typological classification obtained from the previous multivariate analysis. The typological solids revealed complex association patterns regarding the BIF types. Finally, we propose a geological evolution concept model of the study area. This model is comprised of 6 stages describing an evolving sequence since the implantation of the sedimentary depositional environments; the start of the volcanic activity which has contributed with the input dissolved iron oxides; the deposition of banded iron formations (itabirites); formation of a narrow sea with the later deposition of the carbonates which has evolved as a rift basin. The final stage describes the deformational and metamorphic events in the Brasiliano-Pan African orogeny framework. Some aspects regarding the timing of orogeny events are discussed.